Multimodal Ensemble Deep Learning to Predict Disruptive Behavior Disorders in Children - Menon, Sreevalsan S.; Krishnamurthy, K. (Frontiers in Neuroinformatics, 2021)
Oppositional defiant disorder and conduct disorder, collectively referred to as disruptive behavior disorders (DBDs), are prevalent psychiatric disorders in children. Early diagnosis of DBDs is crucial because they can increase the risks of other mental health and substance use disorders without appropriate psychosocial interventions and treatment. However, diagnosing DBDs is challenging as they are often comorbid with other disorders, such as attention-deficit/hyperactivity disorder, anxiety, and depression. In this study, a multimodal ensemble 3D convolutional neural network (CNN) deep learning model was used to classify children with DBDs and typically developing children. The study participants included 419 girls and 681 boys, aged 108 to 131 months who were enrolled in the Adolescent Brain Cognitive Development Study. Children were grouped based on the presence of DBDs (n=550) and typically developing (n=550); assessments were based on the scores from the Child Behavior Checklist and on the Schedule for Affective Disorders and Schizophrenia for School-age Children–Present and Lifetime version for DSM-5. The diffusion, structural, and resting-state functional magnetic resonance imaging (rs-fMRI) data were used as input data to the 3D CNN. The model achieved 72% accuracy in classifying children with DBDs with 70% sensitivity and 72% specificity. In addition, the discriminative power of the classifier was investigated by delineating the cortical and subcortical regions primarily involved in the prediction of DBDs using a gradient class activation map. The classification results were compared with those obtained using the three neuroimaging modalities individually, and a connectome-based graph CNN and a multi-scale recurrent neural network using only the rs-fMRI data.